Which Occupation is Highly Associated with Cognitive Impairment? A Gender-Specific Longitudinal Study of Paid and Unpaid Occupations in South Korea - Chung, Woojin (Int J Environ Res Public Health, 2020)
Background: To examine the associations between paid and unpaid occupations and the risk of cognitive impairment with respect to gender in a middle-aged population using the dataset of a nationally representative longitudinal survey. Methods: Overall, 24,925 observations of 5865 participants aged 45–64 years were sampled from the seven waves of the Korean Longitudinal Study of Ageing (2006–2018). A dichotomous outcome variable was derived based on the Korean version of the Mini-Mental State Examination scores, and occupations were grouped into 12 categories, including three unpaid ones. Sociodemographics, lifestyle, and medical conditions were included as covariates in the mixed logistic regression models. Adjusted odds ratios and predicted probabilities of cognitive impairment were estimated. Results: In the longitudinal models with all-studied covariates, the risk of cognitive impairment was similar between genders but differed across occupation categories for each gender. Moreover, the association between occupation and cognitive impairment varied between genders. Regarding the predicted probability, in men, the retired category exhibited the highest risk of cognitive impairment. However, in women, the highest risk was related to the homemakers category, with the risk being more than five times higher than those in the professionals and related workers category. Conclusions: Public health policies to reduce the risk of cognitive impairment in the middle-aged population need to be designed and implemented with respect to both gender and occupation.